Sudden Stops in Capital Inflows and the Design of Exchange Rate Regimes - Raymond Ritter (Hamburg Institute of International Economics (HWWA), 2003)
A two sector small open economy model developed by Corden (1991, 2002) is used to analyse the impact of sudden stops in capital inflows on an internal and external equilibrium and to explore the merits of disposing of the nominal exchange rate as policy tool in rectifying real exchange rate misalignments. It is shown how the economy's sectoral demand properties determine the extent of recession associated with real exchange rate adjustment that is neither engineered by nominal exchange rate changes nor brought about by a decline in nontraded goods prices. The conclusion is drawn that, when deciding on the design of exchange rate regimes, the structural characteristics of the economy ought to be considered so as to appropriately strengthen its capacity to cope with shocks in the form of negative swings in capital inflows.
Keywords: F41; F32; F31; 330; capital inflows; sudden stops; real exchange rate adjustment; exchange rate regimes; Wechselkurssystem; Kapitalimport; Währungskrise; Konjunktur; Kleines-offenes-Land; Mehr-Sektoren-Modell; Theorie